The impact of COVID-19 on routine child immunisation in South Africa - Sangiwe Moyo; Anushka Ashok; Laura Myers; Rebecca Nyankieya; Saransh Sharma; Ram Prasad (BMC Public Health, 2024)
Abstract Background The COVID-19 pandemic disrupted immunisation programs worldwide, reversing gains that had brought vaccine-preventable diseases largely under control. This study explored the impact of COVID-19 on the uptake of routine child immunisation services in South Africa. Methods We conducted qualitative research using in-depth interviews with 51 purposively selected parents/caregivers of children below the age of five who missed or delayed one or more scheduled immunisation doses in 2020–2022 and with 12 healthcare providers who provided public immunisation services during the pandemic. Results During the pandemic lockdowns, most caregivers perceived the risk of their child being infected with COVID-19 during a clinic visit as more salient than the risk of missing immunisation doses. Caregivers reported minimal exposure to routine immunisation communication, as well as shortages of routine vaccines for children at public health facilities, healthcare workers experienced anxiety and burnout. There was a post-pandemic shift to more active decision-making about immunisation, which had previously been an almost automatic behaviour, leading some caregivers to delay vaccinating their children. There was also evidence of a “bad vaccine” mental model among some caregivers regarding COVID vaccinations, which could lead to doubts about the safety of routine childhood vaccinations. Discussion The shift from default to active decision-making highlights a risk that routine immunisation will backslide in future pandemics. Governments should build resilient health systems at all levels and communicate clearly about the benefits and availability of RIs and the safety of vaccinations in general, alongside supply-side interventions. Conclusion Routine immunisation is widely accepted in South Africa, driven by generational norms and provider recommendations. During the COVID-19 pandemic, many caregivers faced the dilemma of balancing COVID-19 exposure risk with the risk of their child developing a deadly VPD, leading to missed RI visits. This shift to active decision-making highlights a future pandemic risk. Governments should build resilient health systems and focus on understanding and engaging procrastinating and doubtful caregivers. Clear communication about RI benefits and vaccine safety is crucial, as misinformation can lead to distrust in new vaccines.